Quality of life and satisfaction among prostate cancer patients followed in a dedicated survivorship clinic. Issue 9 (23rd December 2014) - Gilbert, Scott M.; Dunn, Rodney L.; Wittmann, Daniela; Montgomery, Jeffrey S.; Hollingsworth, John M.; Miller, David C.; Hollenbeck, Brent K.; Wei, John T.; Montie, James E.
Abstract : BACKGROUND: Integrating quality‐of‐life (QOL) outcomes into clinics may assist providers in identifying and responding to problems experienced by cancer survivors. To date, however, patient‐reported outcomes (PROs) such as QOL are used infrequently to guide care. We integrated QOL assessments into a prostate cancer survivorship clinic and compared recovery and satisfaction among men managed in the survivorship clinic with those followed with more routine care. METHODS: We conducted a before‐after study comparing 235 men treated surgically for prostate cancer who received routine follow‐up care with 102 men managed in a survivorship clinic characterized by point‐of‐care QOL reporting and integration of QOL scores (EPIC) following radical prostatectomy. We then assessed baseline and postprostatectomy QOL at 6 and 12 months, as well as patient satisfaction, and compared outcomes between groups. RESULTS: Although baseline QOL was comparable, scores were generally higher among the survivorship group at 6 months and 1 year compared with those followed with routine care. In particular, sexual function scores were significantly higher among patients managed in the survivorship clinic (52.2 vs 33.6 at 1 year, P  < .01). Satisfaction scores were consistently higher in the survivorship clinic group compared with the routine‐care group (all P  < .05). CONCLUSIONS: Patient QOL and satisfaction were higher among men managed in a survivorship program, suggesting that disease‐specific survivorship clinics that integrate QOL reporting into care pathways may yield better outcomes compared with less tailored approaches to patient care following cancer therapy. Cancer 2015;121:1484–1491. © 2014 American Cancer Society . Abstract : Integrating patient‐reported outcomes such as quality of life into the recovery care of men with prostate cancer is associated with better outcomes. These results indicate that more tailored approaches to evaluating and addressing patient‐reported problems improve care and support survivorship models of care.